Small hydropower development in Ukraine under global climate change patterns: is state economic support sufficient?. (23rd August 2022) - Kurbatova, Tetiana; Sotnyk, Iryna; Kubatko, Oleksandr; Gorbachova, Liudmyla; Khrystiuk, Borys
During the last years, significant changes happened in seasonal river hydrology in Europe due to climate change. Nevertheless, according to the presented analysis, the total water runoff for hydropower generation did not change. The last fact is an important policy implication for small hydropower promotion in Ukraine because it belongs to that region and has similar climate conditions. Having analysed the hydropower potential, the paper describes the main advantages and limitations of implementing small hydropower projects in Ukraine. The cost of electricity generated by a small hydropower plant in Ukraine is determined and compared with the current feed-in tariff. The calculations show that the feed-in tariff is 1.4 times higher than the electricity generation cost, making the implementation of small hydropower plants profitable for investors. Since the state provides sufficient economic support for this sector's development, the financial and non-economic barriers significantly hinder small hydropower plant deployment are considered.